Grain crop defect fixing method based on digital image statistical parameterization. Issue 5 (November 2020) - Kovalev, Andrey; Pribylsky, Alexey
Abstract: The article examines the main stages in the development of a statistical method for localizing and classifying grain crop defects in conditions of low resource consumption of hardware and software of modern agricultural sorting systems. The developed methodology allows: to form a set of coefficients that make it possible to quantify the area under study; the use of the variation coefficient enables to unambiguously assess the homogeneity of the contents of the investigated area; the analysis of the obtained groups of variation coefficients provides for localization of the alleged defect against the general background of the contour, with its contents heterogeneity.